Medication control of flunixin in racing horses: Possible detection times using Monte Carlo simulations. (25th November 2021) - Kuroda, Taisuke; Minamijima, Yohei; Nomura, Motoi; Yamashita, Shozo; Yamada, Masayuki; Nagata, Shunichi; Mita, Hiroshi; Tamura, Norihisa; Fukuda, Kentaro; Kuwano, Atsutoshi; Kusano, Kanichi; Toutain, Pierre‐Louis; et al.
Summary: Background: For medication control in several jurisdictions, withdrawal time is the period of refrain from racing after drug administration. It is set by adding a safety period to an experimental detection time. However, there are no reports of statistical analyses of detection time for the determination of withdrawal time in flunixin meglumine‐treated horses. Objective: To analyse the population pharmacokinetics of flunixin in horses through the generation of a dataset for detection time statistical analysis and predictions via Monte Carlo simulation. Study design: Experimental study. Methods: Drug plasma and urine concentrations following single intravenous administration of flunixin 1.1 mg/kg bodyweight (BW) in 10 horses and multiple administration of q 24 hours for 5 days in 10 horses were measured using liquid chromatography with tandem mass spectrometry (LC‐MS/MS). Data were modelled using a nonlinear mixed effect model followed by Monte Carlo simulation. Irrelevant plasma concentration (IPC) and irrelevant urine concentration (IUC) were calculated using the Toutain approach. Detection times were obtained considering the time after the last administration for selected quantiles of 5000 hypothetical horses under the international screening limit (ISL) proposed by the International Federation of Horseracing Authorities (plasma: 1 ng/mL, urine; 100 ng/mL). Results: For a regimen of 1.1 mg/kg BW q 24 hours, the IPC and IUC values were 2.0 and 73.0 ng/mL respectively. Detection times in plasma above the ISL for 90% of simulated horses were estimated as 74 hours after a single 1.1 mg/kg dose administration, 149 and 199 hours after multiple doses over 5 days at either 24‐ or 12‐hour intervals respectively. Corresponding detection times in urine were 46, 68 and 104 hours respectively. Main limitation: Only female horses were investigated. Conclusions: Statistical detection times for different flunixin meglumine regimens indicated a delay of detection time in plasma after multiple administrations under ISL.